2023
DOI: 10.2174/011871529x250233231017043628
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Heart's Left and Right Ventricles (EF and TAPSE) in CABG Surgery Patients before and after Cardiac Rehabilitation

Mahdi Zahedi,
Fahime Safi

Abstract: Background: Post-coronary artery bypass grafting (post-CABG) is a beneficial procedure for cardiac patients. However, without an appropriate cardiac rehabilitation (CR) program, patient care may be inadequate, leading to recurrent hospitalizations and heart failure. This study aims to assess the effects of a CR program on left ventricular ejection fraction (LVEF) and tricuspid annular plane systolic excursion (TAPSE) measures in post-CABG patients at Amir-almomenin, kordkuy Hospital, Golestan, Iran. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Adherence was 70% for men and 68% for women 12 t-test and ANCOVA Weinberger 2014 [ 86 ] Patients with PTCA, CABG, MI, valve replacement, CAD, CHF, angina or cardiomyopathy n = 1138 (843 men, 295 women) Not described ≥ 7weeks; average 11 weeks CR completion: 49% Adherence was 11.5 weeks for men and 11.4 weeks for women 12 Other (Logistic regression) Willenheimer 1998 [ 38 ] Patients with HF and ejection fraction < 45% n = 33 (27 men, 6 women) Aerobic 16 Weeks CR completion: 91% Adherence for men was 78% and for 67% women 12 t-test Wise 2012 [ 51 ] Patients with CHF (NYHA level I-III) also diagnosed with CAD, cardiomyopathy, valvular disease, and or/tachycardia n = 232 (172 men, 60 women) Aerobic and Strength 12 Weeks + median of 4 extra weeks CR completion: 100% All patients attended at least 40% of sessions. 11 Other (Wilcoxon) Zahedi 2022 [ 74 ] Patients with MI and PCI n = 30 (23 men, 7 women) Aerobic 5 Weeks CR completion: 100% 9 Other (Wilcoxon) Zahedi 2023 [ 73 ] Patients with CABG n = 100 (67 men, 33 women) Aerobic 4 weeks CR completion: 100% 11 Other (Wilcoxon) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence was 70% for men and 68% for women 12 t-test and ANCOVA Weinberger 2014 [ 86 ] Patients with PTCA, CABG, MI, valve replacement, CAD, CHF, angina or cardiomyopathy n = 1138 (843 men, 295 women) Not described ≥ 7weeks; average 11 weeks CR completion: 49% Adherence was 11.5 weeks for men and 11.4 weeks for women 12 Other (Logistic regression) Willenheimer 1998 [ 38 ] Patients with HF and ejection fraction < 45% n = 33 (27 men, 6 women) Aerobic 16 Weeks CR completion: 91% Adherence for men was 78% and for 67% women 12 t-test Wise 2012 [ 51 ] Patients with CHF (NYHA level I-III) also diagnosed with CAD, cardiomyopathy, valvular disease, and or/tachycardia n = 232 (172 men, 60 women) Aerobic and Strength 12 Weeks + median of 4 extra weeks CR completion: 100% All patients attended at least 40% of sessions. 11 Other (Wilcoxon) Zahedi 2022 [ 74 ] Patients with MI and PCI n = 30 (23 men, 7 women) Aerobic 5 Weeks CR completion: 100% 9 Other (Wilcoxon) Zahedi 2023 [ 73 ] Patients with CABG n = 100 (67 men, 33 women) Aerobic 4 weeks CR completion: 100% 11 Other (Wilcoxon) …”
Section: Resultsmentioning
confidence: 99%
“…Eight studies comparing left ventricular ejection fraction in HD patients reported equal improvements between the sexes or no improvements at all after CR [ 28 , 32 , 49 , 50 , 52 , 71 73 ] with a single study finding that men improved to a greater degree than women (only 5 weeks of CR) [ 74 ]. While three studies investigating HR at rest showed a greater improvement in men after CR [ 49 , 72 , 75 ], the majority of the articles investigating HR at rest showed no sex difference or no improvement in either sex [ 27 , 28 , 30 , 31 , 39 , 47 , 50 , 57 , 59 , 64 , 71 , 76 – 80 ].…”
Section: Discussionmentioning
confidence: 99%